Late Adulthood, COVID-19-Related Stress Perceptions, Meaning in Life, and Forgiveness as Predictors of Mental Health During the COVID-19 Pandemic - Toussaint, Loren; Cheadle, Alyssa; Dezutter, Jessie; Williams, David R. (Frontiers in Psychology, 2021)
The purpose of this study was to examine multiple direct and indirect pathways of the association between older age and mental health through COVID-19-related stress perceptions, meaning in life, and forgiveness of situations. Participants were 1,382 U.S. adults who were part of the Harvard Digital Lab for the Social Sciences panel who volunteered to complete a 12 minute survey in the spring of 2020. The sample had an average age of 56 years, was slightly more male (55%) than female (44%) or other (2%), mostly White (88%), well-educated (70% bachelors degree or more), and middle-income ($60,000 - $75,000 annually). Measures included: COVID-19-related stress perceptions (e.g., concerns about infection, job, lack of necessities), presence of and search for meaning in life, forgiveness of situations, psychological distress, hopelessness, and optimism. A latent mental health variable was created that was comprised of psychological distress, hopelessness, and optimism. All hypothesized direct effects were in evidence, and all but one indirect effect were observed. Specifically, older age was related to better mental health through higher presence of meaning and lower search for meaning. Older age was also related to better mental health through a serial indirect pathway from lower COVID-19-related stress perceptions to higher presence of and lower search for meaning and higher forgiveness of situations to mental health. The proposed model was largely supported and confirms existing theory and research on aging, positive psychological processes, and mental health. Findings also offer new insights on the unique potential role of forgiveness of situations and its theoretical relevance to offending situations such as the COVID-19 pandemic. The present study offers a beginning for theorists, researchers, and practitioners to consider the connections between aging and mental health and the intricate interconnections between stress appraisal and positive coping resources that may serve to support it.